4.3k views
4 votes
Please show your work, thx for the help

Please show your work, thx for the help-example-1
User Olivia
by
6.1k points

1 Answer

7 votes

Answer:

A.
(8n^(3))/(m^(4)p^(2))

B.
(1)/(16)

Explanation:

We have to simplify two examples of exponent using the rules.

1) A. The given expression is
(8p^(-2) )/(m^(4)n^(-3))

Now,
(8p^(-2) )/(m^(4)n^(-3))

=
(8)/(m^(4)) * ((p^(-2) )/(n^(-3) ) ) {Since the terms are in product form so, we can treat them separately}

=
(8)/(m^(4)) * ((n^(3) )/(p^(2)))

{Since, using the property of exponents we can write
x^(-a) = (1)/(x^(a)) and
(1)/(x^(-a) ) = x^(a) }

=
(8n^(3))/(m^(4)p^(2)) (Answer)

B. The given expression is
2^(-4). 3^(0)

Now,
2^(-4). 3^(0)

=
(3^(0))/(2^(4))

=
(1)/(2^(4)) {Since,
x^(0) = 1 provide x ≠ 0}

=
(1)/(16) (Answer)

User Psms
by
6.8k points